PEPAD: UM PEPTÍDEO MULTIFUNCIONAL COM ATIVIDADE ANTIFÚNGICA E ANTICÂNCER - Camila de Oliveira Gutierrez (2024)
Fungal infections and cancer represent two distinct threats to human health, but in some cases, they are related. Recurrent fungal infections and those caused by other specific microorganisms can induce the mutation of certain cells and consequently lead to the development of various types of cancer. On the other hand, patients undergoing cancer treatment are immunocompromised, which favors infections by microorganisms. Adding this complex link to the growing resistance of fungi and cancer cells to drugs, the development of new active substances or drugs as therapeutic alternatives becomes necessary. Through the broth microdilution technique, it was observed that PEPAD exhibited activity against 5 species of Candida fungi, with MICs ranging between 2.5 - 5 µM, and showed a rapid action time (60 minutes) against Candida tropicalis. It was also found that its likely mechanism of action is through binding with ergosterol present in the plasma membrane. Furthermore, PEPAD showed synergistic action with the antifungal drugs amphotericin B and fluconazole, significantly reducing the required concentrations of both molecules. Inhibition assays of biofilm formation and eradication of mature biofilm were also conducted, and it was found that PEPAD was able to inhibit and eradicate part of the C. tropicalis biofilm. To evaluate the anticancer potential and toxicity of the peptide, cell viability assays were performed using the colorimetric method with MTT. The IC50 found for murine melanoma cells (B16F10-Nex2) was 7.4 µM, whereas for healthy murine macrophage (RAW 264.7) and human fibroblast (FN1) cells, it was not possible to find the IC50 up to the highest tested concentration (16 µM), suggesting high selectivity and low toxicity. After treatment with PEPAD in murine melanoma cells, no morphological alterations were observed in the cell membrane, but changes in nuclear chromatin were noted, suggestive of apoptosis. Through a scratch assay performed on a cell layer, it was observed that PEPAD delayed the cell migration of melanoma, indicating a potential anti-metastatic effect. To evaluate mitochondrial potential and nuclear morphology, the fluorescent probes MitoTracker Deep Red and NucBlue were used. It was observed that the cell nuclei remained intact; however, mitochondrial swelling was observed. Caspase activation was analyzed using the CaspACETM FITC-VAD-FMK marker, revealing active caspases through the binding of the fluorescent marker to activated caspases in cells undergoing apoptotic death. Flow cytometry experiments were also conducted to confirm the type of cell death. The results support previous findings, indicating that PEPAD induces cell death by apoptosis. Finally, ELISA assays were conducted, and it was found that PEPAD was able to induce the release of calreticulin and HMGB1, which are molecules known as Damage-Associated Molecular Patterns (DAMPs), a typical effect of immunogenic cell death. The results suggest the high potential of PEPAD to be used as a prototype in the development of new antifungal and anticancer agents, given its selective characteristics against microorganisms and cancer cells.